PELATIHAN DETEKSI DINI DAN INTERVENSI GANGGUAN BAHASA DAN BICARA PADA ANAK DISABILITAS - Sudarman, Sudarman; Gunawan, Gunawan (Jurnal Indonesia Mengabdi, 2024)
People with disabilities are people who experience physical, mental, intellectual, or sensory limitations that are experienced for a long period of time. These limitations can cause obstacles and difficulties in participating fully and effectively with society. Physical disabilities experience impaired motor function including amputation, paralysis or stiffness, paraplegia, cerebral palsy, due to stroke. Intellectual disabilities, in this case children with disabilities experience impaired thinking function because their intelligence level is below average so that it can cause language and speech disorders. This community service activity was carried out at the CG-YPPCG Bina Sejahtera Special School in Surakarta City with the aim that parents and teachers have the knowledge and skills in carrying out early detection and intervention in children with disabilities. This community service method uses a counseling and training approach for teachers and parents of students about early detection in children with language and speech disorders. Results: This community service was attended by 50 people consisting of parents of students and school teachers, more than 70% of community service participants have understood how to carry out detection and intervention in children with language and speech disorders